Resistance Detection and Transmission Risk Analysis of Pig-Derived Pathogenic Escherichia coli in East China - Li, Xiaoting; Liu, Haibin; Cao, Sai; Cheng, Ping; Li, Fulei; Ishfaq, Muhammad; Sun, Jichao; Zhang, Xiuying (Frontiers in Veterinary Science, 2021)
Objective: Antibiotics play an essential role in the treatment and prevention of diseases in pig farms. However, the irrational use of antibiotics leads to the emergence of multi-drug resistance of bacteria, which poses a critical threat to the efficacy of antibiotic treatments. Therefore, the study is designed to analyze the drug resistance of pathogenic Escherichia coli (E. coli) isolated from large-scale pig farms in East China, which provides a theoretical basis for precisely targeted clinical drugs in swine farms. Method: The pathogenic E. coli were isolated and identified from clinical samples of swine farms, and the drug resistance of pathogenic E. coli was detected by antimicrobial susceptibility test (AST) and minimum inhibitory concentration test (MIC). Moreover, the prevalence of plasmid-mediated β-lactam resistance genes was analyzed by PCR. Results: A total of 67 pathogenic E. coli were isolated from 152 samples collected from 20 large-scale pig farms in East China. All isolated pathogenic E. coli are associated with severe drug resistance. Moreover, 70% of isolated pathogenic E. coli is resistant to more than four antibiotics. Besides, there were 19 serotypes including O2, O4, O5, O6, O14, O26, O38, O42, O49, O57, O92, O93, O95, O101, O121, O131, O143, O158 and O161, of which the O4 and O92 serotype were the main serotypes in swine farms. The main extended-spectrum beta-lactamases (ESBLs)-encoding genes in East China were blaCTX-M, blaTEM and blaOXA by the detection of the ESBLs encoding genes of porcine pathogenic E. coli. The conjugation assays showed that a total of 30 transconjugants were obtained by conjugation, which indicated that drug resistance genes could be transmitted horizontally through conjugative plasmids. Conclusion: The isolated pathogenic E. coli were all multi-drug resistant, and especially O4 and O92 were the main serotypes. The β-lactam resistance genes were prevalent in large-scale pig farms in East China, which provided a theoretical basis for the prevention and control of pig-derived pathogenic E. coli in the future.